The Encounter of Arabic Intellectual Discourses with Modernity: An Introduction and Critique of Book of Arabic and Modernity: A Study in the Discourse of Modernists - Mohammad Ali Tavana (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Abdal-llah Belqiziz, a Moroccan philosopher in Arabic and Modernity: A Study of Modernist Discourse, poses the question of how he encountered Arab intellectual discourses (authentic, reformist, and liberal) with modernity and why these discourses have not succeeded in opening the way to Arab modernity? According to Belqiziz, the main problem goes back to the theoretical framework of these discourses, which contains the following problems: 1. A mechanical definition of the relationship between oneself and another; 2- Linear view of history; 3- Incomplete understanding of modernity. In contrast to Belqiziz, the discourse of critical rationalism is the solution to these problems because of its reliance on the internal dialectic between self and the other, self and the other dialectical critique, nonlinear view of history (simultaneous intellectual history), cultural understanding of modernity, avoidance of absolutism, as well as the possibility of combining Western and Islamic. However, it seems that Belqiziz’s solution still has two fundamental problems: 1- The inevitability of modernity; 2- Lack of pure indigenous epistemological system and methodology for the transition to progress.